Écriture, cadre, contexte - Isabelle Delcambre (Multilinguales, 2013)
Numerous theoretical studies in different research fields establish the variability of meaning and use of the notion of context. Some debates around this notion are first briefly exposed, before coming to the notion of frame, which is not unrelated to that of context. We will show that disciplines can be seen as frames (or contexts) that are interacting with writing practices. Finally, the notion of discursive framework is useful in a didactic perspective to make students more aware of some characteristics of academic writing.